The Russian Cyber‐Bride as Geopolitical Fantasy. (April 2016) - Klinke, Ian
Abstract: This article unpacks the fantasy of the Russian online bride and its striking contamination with geopolitical language. Drawing on critical geopolitics and psychoanalysis, it explores the economy of desire and anxiety that accompanies British men's quest for sexually available 'traditional' housewives that are still untouched by 'modern' feminism. The paper argues that these men desire the slippery substance of Easternness – an ideal object of desire which is too elusive to be conquered or held. The paper thereby inverts existing accounts of the sexualised nature of the geopolitical gaze to expose the traces of geopolitics in sexual fantasies themselves. In doing so, it formulates the basis for a triadic understanding of otherness.